2021
DOI: 10.2174/1389201021999200918102123
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Wound Healing Potential of Essential Oil from Citrus reticulata Peel and Its Chemical Characterization

Abstract: Background: Fruit peels are considered as waste and contribute towards a major proportion of biomass. They might be a good source of various therapeutic benefits. Peels biomass of citrus fruits are usually considered as garbage. Such peels may have many important and valuable medicinal components with pharmacological activities. Citrus reticulata, (of family Rutaceae, local name tangerine) is a local seasonal fruit in Pakistan which is a very good example regarding wastage of its peels. Objective: The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, a hydrodistillation method was employed to extract EO from Blanco peel, mainly constituted by limonene (89.31%), which exhibits antibacterial activity against Cutibacterium acnes and common microorganisms such as S. aureus , B. subtilis and E. coli [ 79 ]. In addition, besides the antimicrobial potential, EO from C. reticulata peel has been able to significantly reduce wound diameter in vivo, thus showing wound healing property [ 80 ]. Mandarin peels contain also a high total flavonoid content compared to lemon and grapefruit peels, and have been demonstrated to possess moderate cytotoxic activity against the HL-60 cell line, an experimental model of acute myeloid leukemia [ 81 ].…”
Section: Citrus Reticulata Blanco and Its Hybridsmentioning
confidence: 99%
“…However, a hydrodistillation method was employed to extract EO from Blanco peel, mainly constituted by limonene (89.31%), which exhibits antibacterial activity against Cutibacterium acnes and common microorganisms such as S. aureus , B. subtilis and E. coli [ 79 ]. In addition, besides the antimicrobial potential, EO from C. reticulata peel has been able to significantly reduce wound diameter in vivo, thus showing wound healing property [ 80 ]. Mandarin peels contain also a high total flavonoid content compared to lemon and grapefruit peels, and have been demonstrated to possess moderate cytotoxic activity against the HL-60 cell line, an experimental model of acute myeloid leukemia [ 81 ].…”
Section: Citrus Reticulata Blanco and Its Hybridsmentioning
confidence: 99%
“…Pear fruit peels also produced cinnamtannins B1 (130), aesculitannin A ( 131) and (−)-epicatechin-(4β→6)-(−)-epicatechin-(4β→8, 2β→O→7)-(−)-epicatechin (132) [95] and these proanthocyanidin trimers displayed anticancer, antibacterial and antioxidative effects [96][97][98][99]. (136) and quercetin (137) (Figure 16). The flavones 135 and 136 illustrated antioxidant effects with IC50: 43.5 and 39.1 µ g/mL, respectively [100].…”
Section: Flavones Flavanone and Condensed Tanninsmentioning
confidence: 99%
“…It was found that isovitexin (145), vitexin (146), orientin (147), vitexin-2′′-Orhamnoside (148) and vitexin-4′′-O-glucoside (149) were reported from Benincasae exocarpium fruit peels and screened for antidiabetic effects. (136) and quercetin (137) (Figure 16). The flavones 135 and 136 illustrated antioxidant effects with IC 50 : 43.5 and 39.1 µg/mL, respectively [100].…”
Section: Flavones Flavanone and Condensed Tanninsmentioning
confidence: 99%
See 1 more Smart Citation
“…. There are abundant volatile oil and flavonoids observed in CRCP, of which volatile oil has been proven to be the characteristic substance contributing to the aroma of CRCP and possessing antioxidant properties (Ishfaq et al, 2021). The flavonoids are primarily divided into dihydroflavones and polymethoxyflavones (PMFs) (Tistaert et al, 2011), and the phytochemical studies have illustrated that the flavonoids could regulate gut microbiome and perform anti-tumor, anti-neuroinflammatory activities (Duan et al, 2017;Ho and Kuo, 2014;Zeng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%